2009
DOI: 10.1159/000235977
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Risk for Attrition during Treatment for Depression

Abstract: Background: Understanding patients’ ambivalence about treatment persistence may be useful in tailoring retention interventions for individual patients with major depressive disorder. Methods: Participants (n = 265) with major depressive disorder were enrolled into an 8-week trial with a selective serotonin reuptake inhibitor. At baseline and week 2, the participants were asked about their intent to return for the next visit, complete the study and continue in the study should they experience side effects or no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 90 publications
(53 reference statements)
1
19
1
Order By: Relevance
“…This might in part explain dropout in the present sample as well. In line with Warden et al [34], we acknowledge that an individualized review of concerns and tailoring of appropriate interventions may be necessary to reduce attrition.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…This might in part explain dropout in the present sample as well. In line with Warden et al [34], we acknowledge that an individualized review of concerns and tailoring of appropriate interventions may be necessary to reduce attrition.…”
Section: Discussionsupporting
confidence: 54%
“…Analyses showed that for dropouts less improvement was reported than for patients continuing therapy, suggesting range restriction operating in the criterion measure. Recently, Warden et al [34] found that participants’ pretreatment concerns about continuing antidepressant treatment in the presence of side effects signals challenges to the completion of a full 8-week acute-phase treatment, even if the participant does not develop side effects. This might in part explain dropout in the present sample as well.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Warden et al [72] indicated that the initial intent of the patient with respect to continuing treatment is more relevant for drop-out than perceived side effects or a lack of efficacy during treatment. Discussing intent with patients at risk of drop-out before the start of therapy could therefore enhance adherence, alongside telephone support [66] and motivational interviewing [73].…”
Section: Discussionmentioning
confidence: 99%
“…This can signal challenges to the completion of an acute phase treatment, as a recent study of Warden et al [29] has shown. The use of the HAMD-17 as a measure of outcome might be another limitation [30].…”
Section: Discussionmentioning
confidence: 99%